A Study of Shanghai Tourist Destination Brand Equity: Perspectives from Western Group Tourists - SHEN, Li; MA, Jianyu (Journal of Tourism Management Research, 2022)
This study examines western group tourists’ perceptions of city destinations in China and measures destination brand equity for Shanghai as a city tourism destination in China’s inbound market. The study investigated 420 Western group tourists and verified the path relation between the constituent elements of Shanghai's tourism destination brand equity. It examined the influence of four independent variables (brand awareness, brand image, brand quality and brand value) on the dependent variable (brand loyalty). The findings suggest that only brand quality has direct and significant impact on brand loyalty, while brand awareness, brand image and brand value affect brand loyalty indirectly through brand quality. It is also found that genders, number of visits, and tourists of different occupations have significant different evaluations in the brand awareness. There are significant differences in the brand value between different household incomes and tourists in different regions. This research provides suggestions for tourism destination brand building and management in Shanghai, such as a guaranteed high-level qualified experience for travelers, increasing the brand awareness among Westerners through cross-cultural communication via global social media.